World History for International Studies - Duyvesteyn, Isabelle; van der Wal, Anne Marieke (Leiden University Press, 2022)
Studying change in the course of human history, in different places, through the lens of a diverse set of core themes, World History for International Studies offers readers a set of windows into different debates historians have been conducting. Key themes, such as communication, trade, order, slavery, religion, war, identity, modernity, norms and ecology, are linked to specific world regions, which tell a story about how local ideas and individual contacts developed, started to overlap and became globally understood and used by ever larger groups of people. These themes are brought to life by a diverse set of key primary sources, such as a book, a letter, a medal, a temple and an epic, to showcase how historians have used sources to tell these stories and conduct debates. The book provides an introductory resource into the study of history and includes detailed suggestions for further study.